Degree of math teacher practice for brain-based learning strategies. - ismaeelsari, Randa; Nawaf Alali, shiras (Journal of Social Sciences and Humanities, 2025)
The objective of the research is to recognize the degree of mathematics teachers practice of brain-based learning strategies, and the number of sample members has reached (50) A mathematical teacher and teacher from the Rif Dimascus governorate, disaggregated by sex into (23) teachers and (27) teachers, distributed according to the scientific qualification variable to (12) Diploma, (16) University Bachelor's Degree, (14) Institute of Teacher Training, (6) Master's Degree and (2) Doctorate, distributed by variable years of service to (15) less than Less (5) years and (17) of 5 - 10 years, and (18) More than 10 years, the researcher used the analytical descriptive approach, and the researcher designed a resolution consisting of (25) To identify the degree of mathematics teachers' practice of brain-based learning strategies, The results concluded that the degree of mathematics teachers' exercise of brain-based learning strategies was moderate and also found that there were no statistically significant differences between average math teachers' identification of brain-based learning strategies depending on sex variable, scientific qualification and years of experience.